Global Real-World Outcomes of Patients Receiving Immuno-Oncology Combinations for Advanced Renal Cell Carcinoma: The ARON-1 Study - Santoni, Matteo; Massari, Francesco; Myint, Zin W; Iacovelli, Roberto; Pichler, Martin; Basso, Umberto; Kopecky, Jindrich; Kucharz, Jakub; Buti, Sebastiano; Rizzo, Mimma; Galli, Luca; Büttner, Thomas; et al. (Targeted oncology, 2023)
BACKGROUND: Immuno-oncology combinations have achieved survival benefits in patients with metastatic renal cell carcinoma (mRCC). OBJECTIVE: The ARON-1 study (NCT05287464) was designed to globally collect real-world data on the use of immuno-combinations as first-line therapy for mRCC patients. PATIENTS AND METHODS: Patients aged ≥ 18 years with a cytologically and/or histologically confirmed diagnosis of mRCC treated with first-line immuno-combination therapies were retrospectively included from 47 International Institutions from 16 countries. Patients were assessed for overall survival (OS), progression-free survival (PFS), and overall clinical benefit (OCB). RESULTS: A total of 729 patients were included; tumor histology was clear-cell RCC in 86% of cases; 313 patients received dual immuno-oncology (IO + IO) therapy while 416 were treated with IO-tyrosine kinase inhibitor (IO + TKI) combinations. In the overall study population, the median OS and PFS were 36.5 and 15.0 months, respectively. The median OS was longer with IO+TKI compared with IO+IO therapy in the 616 patients with intermediate/poor International mRCC Database Consortium (IMDC) risk criteria (55.7 vs 29.7 months; p = 0.045). OCB was 84% for IO+TKI and 72% for IO + IO combination (p < 0.001). CONCLUSIONS: Our study may suggest that immuno-oncology combinations are effective as first-line therapy in the mRCC real-world context, showing outcome differences between IO + IO and IO + TKI combinations in mRCC subpopulations. CLINICAL TRIAL REGISTRATION: NCT05287464.
Keywords: doba přežití bez progrese choroby; Progression-Free Survival; inhibitory proteinkinas; retrospektivní studie; Humans; karcinom z renálních buněk; Retrospective Studies; nádory ledvin; Protein Kinase Inhibitors; Carcinoma, Renal Cell; Kidney Neoplasms; lidé